THE POTENCY OF PULUTAN (Urenalobata L.) LEAVES DECOCTION AS ANTIFERTILITY BASED ON ITS EFFECT ON UTERINE DEVELOPMENT OF BALB C MICE (Musmusculus) - Handayani, Nursasi; Gofur, Abdul (Jurnal Kedokteran Hewan, 2017)
The purpose of this research was to determine the effect of decoction of pulutan leaves simplicia(Urenalobata L.) on the development of the uterus of Balb C mice (Musmusculus). Female mice aged 10-12 weeks were given decoction of pulutan leaves simplicia with concentration of 5%, 7.5%, 10%, 12.5%, 15%, and control. The administration of pulutan leaves was performed by gavage for 11 consecutive days. On day 12, mice were dissected, then, the uterus was taken for histological preparations using paraffin method. Data such as uterine diameter and myometrium and epimetrium thickness were analyzed using one way analysis of variance followed by least significant different. The results showed that decoction of pulutan leaves simplicia decrease the uterine diameter and epimetrium and myometrium thickness compared to control. The decrease of uterine diameter and uterine myometrium and epimetrium thickness was started at the concentration of 7.5%. Decoction of pulutan leaves simplicia could reduce uterine diameter and thickness of uterine myometrium and epimetrium, thus, it might decrease the uterine function as the site of implantation. The decline in the function of the uterus might decrease the number of born children, thus decoction of pulutan leaves simplicia is potential as antifertility agent.